Web-based assessment of dual-task costs at different ages: an analysis across cognitive domains - Livoti, Vincenzo; Del Popolo Cristaldi, Fiorella; Contemori, Giulio; Saccani, Maria Silvia; Bonato, Mario (Frontiers in Psychology, 2025)
IntroductionUnderstanding the trajectories of cognitive aging provides important insights that might also be potentially useful for the early detection of cognitive impairments. Among many, multitasking abilities are particularly relevant in everyday life contexts across the adult lifespan.MethodsWe used web-based, self-administered, dual-tasks to measure performance and dual-task costs (DTCs) at different ages, accounting for the influence of cognitive efficiency and cognitive reserve. We also tested whether DTCs were task-specific or related to general abilities by employing three dual-tasks, each focused on different cognitive functions. We measured the performance of ﻿419 Italian-speaking healthy participants (18–76 years old) in: (i) a digital version of the Trail Making Test (A + B); (ii) the divided-attention subtest of the Test of Attentional Performance battery, adapted for online administration; (iii) a visuo-mnestic dual-task, validated in previous studies with healthy younger and older adults.ResultsResults showed that with increasing age and cognitive load performance significantly reduced across all tasks. DTC for TMT and MEMO showed a small yet non-linear age-related increase. Global cognitive functioning and cognitive reserve demonstrated a weak, negative association with DTCs across all tasks, suggesting a secondary role in mediating multitasking performance. DTCs correlations across tasks were very weak, supporting the hypothesis of task-specificity for multitasking abilities.DiscussionThese findings highlight the feasibility of web-based testing while also emphasizing the heterogeneity ﻿of both age-related cognitive change and the cognitive processes involving dual-task performance.﻿﻿﻿